Sentir lo indecible. Sentido, sin sentido y carencia de sentido en el Tractatus de Wittgenstein - Sanfélix Vidarte, Vicente (Revista de Filosofía, 2009)
This article analyses Wittgenstein’s conception of nonsense and, against resolute interpretations, defends that, perhaps influenced by Mauthner and Weininger, the Tractatus author conceived corrects ontological and ethical nonsenses like nearly to tautological senseless.